Florence and the river: new urban perspectives - Alberti, Francesco; Paloscia, Raffaele (International Journal of Engineering and Technology, 2018)
The upgrading of riverfronts is a theme that has long played a central role in the renewal programs of large, medium and small cities throughout Europe. The case study presented in this paper is Florence, whose Roman origins and development, from the Middle Ages to today, are closely linked to the Arno River, which runs from east to west. After briefly reviewing some salient moments in the history of the relationship between the city and the river, the paper illustrates some research and projects carried out within the Department of Architecture of the University of Florence, focused on the role that Arno can still play in the future of the Florentine metropolitan area, as a catalyst for interventions aimed at improving urban sustainability, livability and resilience to climate change.